A simple, effective and inexpensive method to isolate the nucleic acid (DNA/RNA) from a single tick for molecular detection of various pathogens - Bhatia, Sudhir; Baersch, Gudrun (The European Research Journal, 2024)
Objectives: Ticks are vectors of a number of pathogens, which cause diseases with fatal consequences, therefore it is essential to detect such pathogens from single tick. Molecular methods like polymerase chain reaction (PCR) are offering such possibilities. At present, cumbersome methods involving liquid nitrogen, cutting ticks with scalpels as well as pooled ticks are being used worldwide. Our goal is to develop a reliable and fast method to obtain nucleic acid (DNA/RNA) from the single tick shipped at room temperature to detect various pathogens. Methods: We developed a mechanical crushing method with mini column nucleic acid isolation from a single tick shipped at room temperature with postal or currier service in a letter. PCR detection was done for Borrelia burgdorferi and tick-borne encephalitis virus as examples. Results: This method was used successfully for the isolation of nucleic acid from single tick and later used for PCR detection of B. burgdorferi and tick-borne encephalitis virus on 17 single tick samples as examples, but for last 18 years, this method was used on more than 250 ticks from Germany. Spectrometric values indicate the presence of sufficient yield of DNA and RNA (up to 900 µg/mL per tick) during the isolation. Conclusions: This may be the first report about a number of one single tick cases, which were sent at room temperature in letters with postal services for isolation of the nucleic acid with mini column kit and used later on for PCR detection of various pathogens. This inexpensive and simple method may be used in any laboratory worldwide for monitoring the presence of tick-borne pathogens.